2019
DOI: 10.1177/1477153518824147
|View full text |Cite
|
Sign up to set email alerts
|

A practical metric for melanopic metrology

Abstract: Over the past decade, there has been a growing interest in lighting research on the effects of the recently discovered melanopsin receptor (also referred to as the intrinsically photosensitive retinal ganglion cell) and its impacts on health and vision. Presently, there is not a generally accepted metrology for dealing with the spectral response of the melanopsin receptor as applied to both lighting and vision research. A proposition to handle this issue from a vision science perspective has been presented in … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
9
0

Year Published

2019
2019
2025
2025

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(14 citation statements)
references
References 25 publications
0
9
0
Order By: Relevance
“…The melanopic ELR, i.e. the melanopic efficacy of luminous radiation, is similar to the the M/P ratio method proposed elsewhere 74 .…”
Section: Methodsmentioning
confidence: 82%
“…The melanopic ELR, i.e. the melanopic efficacy of luminous radiation, is similar to the the M/P ratio method proposed elsewhere 74 .…”
Section: Methodsmentioning
confidence: 82%
“…Recently, a modified version of another commercial actimeter has been developed (Condor, ActTrust model code AT0503LF, or ACTmod) with a 17,6% spectral mismatch to the melanopic action spectrum, using a single sensor, and with a 13,5% spectral mismatch to V(λ), using a second sensor (Price and Lyachev, 2017b). With these two sensors, it should be possible to collect exposure data that are reusable for a greater range of the non-visual spectral response models than using melanopic data alone, including recently proposed melanopic/photopic models (Berman and Clear, 2019).…”
Section: Discussionmentioning
confidence: 99%
“…M/P = 1 describes the light source that has equal melanopic and photopic intensities, and thus, equal visual and non-visual effects. When M/P > 1, the light source has higher melanopic intensity; when M/P < 1, photopic intensity is higher than melanopic intensity [63]. The results showed that bluish SPs could increase the intensity and distribution of melanopic luminance and CCT inside spaces, while reddish SPs could increase the photopic luminance intensity and distribution and reduce CCTs.…”
Section: Shading Devices and External Obstructionmentioning
confidence: 92%